1999
DOI: 10.1111/j.1540-8159.1999.tb00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker Interference with Screening Mammography

Abstract: In female pacemaker recipients undergoing screening mammography, the impact of a pulse generator placed in the pectoral region has yet to be reviewed. We evaluated mammograms from 74 female pacemaker patients aged 40 years and older. The pulse generator obscured a portion of the mammogram in 7 patients (12%). During pacemaker implantation in women, the potential for the pulse generator to interfere with screening mammography should be considered. Baseline mammography should be obtained or reviewed; in high ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Several authors could demonstrate that shock waves applied during extracorporeal shock wave lithotripsy (ESWL) have no influence on ICD function, even when the generators have been exposed to the focal point of the wave 2–4 . In contrast, diagnostic radiation (screening mammography) 5 and therapeutic radiation showed different modes of interference with pacemakers 6 and ICDs 7 depending on the integrated circuit (IC) technology of the devices. Therapeutic diathermy may cause problems by heating the device or burning the tissue close adjacent to the ICD 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Several authors could demonstrate that shock waves applied during extracorporeal shock wave lithotripsy (ESWL) have no influence on ICD function, even when the generators have been exposed to the focal point of the wave 2–4 . In contrast, diagnostic radiation (screening mammography) 5 and therapeutic radiation showed different modes of interference with pacemakers 6 and ICDs 7 depending on the integrated circuit (IC) technology of the devices. Therapeutic diathermy may cause problems by heating the device or burning the tissue close adjacent to the ICD 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific literature, little is known about mammography in females with an IMD. Roelke et al 3 report that part of the mammogram was obscured in 12% of the females with a pacemaker. To our knowledge, this is the only study that has reported on the mammographic image quality in females with an IMD.…”
Section: Introductionmentioning
confidence: 99%